Techno-economic evaluation of meshed distribution network planning with load growth and expansion with multiple assets across multiple planning horizons - Altamimi, Abdullah (Frontiers in Energy Research, 2024)
The smart grid paradigm has ushered in an era where modern distribution systems are expected to be both robust and interconnected in topology. This paper presents a techno-economic-based sustainable planning (TESP) strategy, which can be used as a planning framework for linked distribution systems, seeking to discover a realistic solution among competing criteria of diverse genres. In this comparative analysis-based study, three voltage stability assessment indices -VSA_A, VSA_B, and VSA_W -and a loss minimization condition (LMC)-based framework are used in the initial stage to achieve optimal distributed generation (DG) based asset optimization for siting, followed by sizing. The respective techniques are evaluated across two variants of multiple load growth horizons, spread across 10 years. The suggested TSEP technique is tested on two variants of mesh-configured microgrid (MCMG) with varied load growth scenarios. One variant considers a 65-bus MG with fixed load growth of 2.7% across two load growth horizons. The other variant considers a 75-bus MG with varied load growth across four load growth horizons, encapsulating an expansion-based planning perspective. The numerical results of the suggested TESP approach in a comparative study demonstrate its effectiveness, and it can be used by researchers and planning engineers as a planning framework for interconnected distribution tools across multiple planning horizons. The proposed study would contribute to enhancing the robustness and interconnectivity of smart grid distribution systems. This dual focus could lead to more cost-effective and reliable power distribution systems.